Elderly Ages in Liver Transplantation: Are Older Donors Really Higher Risk? - Sangeeta Satish, MD; Chase J. Wehrle, MD; Mingyi Zhang, MD; Mazhar Khalil, MD; Chunbao Jiao, MD; Keyue Sun, MD; Jiro Kusakabe, MD, PhD, MPH; Antonio D. Pinna, MD; Masato Fujiki, MD, PhD; Charles Miller, MD; Koji Hashimoto, MD, PhD; Andrea Schlegel, MD (Transplantation Direct)
Background. There is currently a supply and demand mismatch in liver transplantation, with more patients needing transplants than grafts available. The use of older donors is one potential way of expanding access to viable grafts. No national study has yet reported on outcomes of liver transplants with donors ≥70 y. Methods. The US Scientific Registry of Transplant Recipients registry was queried for deceased donor LT (1988–2021). Balance-of-risk (BAR) score was calculated for each patient. The primary outcome was graft survival. Cubic spline curves were used to evaluate the full spectrum of donor ages. Results. A total of 148 960 livers met inclusion criteria: 5414 (3.6%) from donors ≥70 y and 4291 (2.9%) recipients ≥70 y. Within the overall cohort, graft survival decreased with increased donor and recipient age. Median graft survival within donors ≥70 y improved over time from 2.2 y (interquartile range [IQR] 0.2–9.8 y) in 1987–1999 to 9.6 y (IQR 3.2–11.6 y) in 2010–2019 (P < 0.0001). Elderly donors had equivalent outcomes to donors <70 y when transplanted in elderly recipients (≥70 y). Outcomes for young recipients that received grafts from elderly donor improved with time, with median survival of 10.1 y (IQR 3.9–11.5 y) in 2010–2019. BAR and survival outcomes following liver transplant (SOFT) scores predicted improved graft survival on time-to-event analysis in all donors aged >70 y. In low-risk recipients, evidenced by preallocation SOFT score <5, elderly donors had comparable outcomes to young (<40 y) and middle-aged donors (40–69 y). Increasing donor age was not associated with worse graft survival in transplants performed between 2010 and 2019. Conclusions. Donors aged ≥70 y may be more comfortably considered for deceased donor liver transplantation, especially within low-risk recipients. The BAR and SOFT scores may be a useful guide for safely expanding the use of these theoretically riskier liver grafts.